Information Literacy: Writing Scientific Articles In Collegetall - Juni Syaputra; Vismaia S Damaianti; Dadang S Anshori; Andoyo Satromiharjo; Hakiki Elvionika (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Students tend to experience difficulties in writing scientific papers due to a low reading and writing literacy culture, less than optimal interaction with texts, students' tendency culture, less than optimal interaction with texts, students' tendency to copy other people's work and then claim it as their work, self-correction that is not carried out, and not knowing the phases in writing scientific work. This problem is based on poor information literacy skills. Information literacy is the most important part of the process of writing a scientific paper. This study aims to describe information literacy in writing scientific articles in tertiary institutions. The method used in this research is the descriptive method. The data used in this study are the obstacles faced by students in writing scientific articles. Data sources of information literacy were obtained by distributing questionnaires to students. The data analysis technique used is to calculate the percentage of problems in writing scientific articles and the sources of information literacy used. The next step is to group the results of the questionnaire into the data tabulation table. The results showed that the problems encountered in writing scientific papers in the form of articles were lack of understanding of how to write works well 63.5%, difficulty developing ideas 98.4%, difficulty writing introductory sections 97.6%, difficulties in conducting discussions 67.2 %. While the results of student information literacy sources were obtained from the Google application 57.2%, 19% were obtained through Google Scholar, 12.8% from books, and 11% from other sources.